Active energy ray curable composition, laminate, and method for producing laminate

By using specific compounds in active energy ray curing compositions, the problem of difficult to achieve high chemical protection in harsh environments in the prior art is solved, and efficient chemical and climate protection effects are achieved while maintaining good adhesion and wear resistance.

JP7658516B2Active Publication Date: 2025-04-08DIC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024540766
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-03-09
Filing Date
2024-02-15
Publication Date
2025-04-08
Estimated Expiration
2044-02-15

AI Technical Summary

Technical Problem

The prior art is difficult to provide efficient chemical and climate protection in harsh environments, especially outdoors and around automobiles, and there is a lack of research on chemical protection of active energy ray curing compositions.

Method used

The adhesion and weather resistance of the substrate material and coating agent are improved by using active energy ray curing compositions containing chain carbonyl alkyl propionate and compounds containing isocyanurate or alkazineate bonds.

Benefits of technology

It achieves high chemical protection and weather resistance in harsh environments while maintaining good adhesion and wear resistance, suitable for external applications of automotive and building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658516000001
    Figure 0007658516000001
  • Figure 0007658516000002
    Figure 0007658516000002
  • Figure 0007658516000003
    Figure 0007658516000003
Patent Text Reader

Abstract

An objective of the present invention is to provide an active energy ray curable composition capable of forming a cured coating or cured layer having weather resistance and chemical resistance and with an outstanding appearance, as well as a laminate having the cured layer and a method for manufacturing the laminate. The present invention relates to the active energy ray curable composition characterized by containing a compound (A) comprising a chain hydrocarbon group having 2 to 12 carbon atoms and two (meth)acryloyloxy groups, and a compound having an isocyanurate bond or an allophanate bond.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an active energy ray-curable composition, a laminate, and a method for producing the laminate. [Background technology]

[0002] Resin materials, especially transparent resin materials such as polycarbonate, are used widely in many fields, taking advantage of their characteristics of low specific gravity, light weight, easy processing, and high impact resistance compared to inorganic glass. In addition, resin primers are applied to glass and metal steel sheets for the purpose of coloring, preventing rust, and bonding with other materials. However, resin materials and resin primers have drawbacks such as their surfaces being easily scratched, losing gloss and transparency, being easily corroded by organic solvents, poor weather resistance (e.g., light stability against ultraviolet rays, etc.), and poor heat resistance. Therefore, resin materials are often used after being covered with various protective films in order to improve their surface properties. Examples of such protective films include hard coat layers formed by curing active energy ray-curable compositions.

[0003] Resin materials used outdoors require excellent weather resistance. Patent Document 1 discloses an active energy ray-curable composition that combines adhesion, abrasion resistance, and weather resistance, which contains inorganic oxide fine particles, a poly[(meth)acryloyloxyalkyl]isocyanurate having at least two (meth)acryloyl groups in the molecule, a urethane poly(meth)acrylate having at least two (meth)acryloyl groups in one molecule and an alicyclic skeleton, an alkyl di(meth)acrylate having 4 to 12 carbon atoms, and a photopolymerization initiator in specific ratios. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-10921 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, resin materials, resin primers and active energy ray curable compositions that can be used in harsh environments such as outdoors and around automobiles are required to have not only weather resistance and abrasion resistance but also resistance to acid rain and automobile battery fluid, i.e., excellent chemical resistance. However, the invention described in the above Patent Document 1 does not consider chemical resistance. In addition, the composition described in Patent Document 1 contains an organic monomer that is highly corrosive to substrates, such as an alkyl di(meth)acrylate having 4 to 12 carbon atoms, and therefore when a resin substrate such as a polycarbonate that is susceptible to corrosion or various resin primers is used, the composition may excessively corrode these, resulting in poor appearance of the coating film and deterioration of weather resistance. Therefore, the invention described in Patent Document 1 does not solve both the problems of chemical resistance and weather resistance, and does not enable the formation of a coating film or cured film with a good appearance.

[0006] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide an active energy ray-curable composition capable of forming a cured coating film or cured layer that has weather resistance and chemical resistance and is excellent in appearance, as well as a laminate having the cured layer and a method for producing the laminate. [Means for solving the problem]

[0007] As a result of extensive research, the inventors have found that the above-mentioned problems can be solved by using an alkane di(meth)acrylate compound, which is effective in improving adhesion and weather resistance, in combination with a compound having an isocyanurate bond or an allophanate bond, which can suppress the corrosion of the alkane di(meth)acrylate against resin substrates and resin primers, and have thus completed the present invention.

[0008] That is, the present invention provides the following inventions. (1) An active energy ray-curable composition comprising a compound (A) having a chain hydrocarbon group having 2 to 12 carbon atoms and two (meth)acryloyloxy groups, and a compound having an isocyanurate bond or an allophanate bond. (2) The active energy ray-curable composition according to (1), wherein the compound having an isocyanurate bond or an allophanate bond is a urethane (meth)acrylate compound (B) having an isocyanurate bond or an allophanate bond. (3) The active energy ray-curable composition according to (2), further comprising a (meth)acrylate compound (C) having an isocyanurate bond. (4) The urethane (meth)acrylate compound (B) having an isocyanurate bond or an allophanate bond has, in addition to an isocyanurate bond, an allophanate bond and a (meth)acryloyl group, -OC(=O)-(CH2) in the structure. nA (nA represents an integer of 1 to 6), and a compound (B1) having, in addition to an isocyanurate bond, an allophanate bond, and a (meth)acryloyl group, -OC(=O)-(CH2) in the structure. nA (nA represents an integer of 1 to 6). (5) The active energy ray-curable composition according to any one of (1) to (4), further comprising a compound (D) containing four or more (meth)acryloyl groups in one molecule. (6) The active energy ray-curable composition according to any one of (1) to (5), wherein the active energy ray-curable composition does not contain an organic solvent or contains an organic solvent in an amount of 30 mass% or less based on the total amount of the composition. (7) A laminate having a cured layer of the active energy ray-curable composition according to any one of (1) to (6). (8) A method for producing a laminate, comprising: step 1 of applying any one of the active energy ray-curable compositions (1) to (6) onto a substrate to obtain a coating film; and step 2 of irradiating the coating film with active energy rays to cure a part or the whole of the coating film. (9) The method for producing a laminate according to (8), wherein after the step 2, the step 1 and the step 2 are repeated in this order at least once or more. Effect of the Invention

[0009] According to the active energy ray curable composition of the present invention, it is possible to form a cured coating having excellent chemical resistance and high weather resistance while satisfying the properties required for the cured coating, such as adhesion and abrasion resistance, and having an excellent appearance. This cured coating has excellent adhesion to resin substrates such as polycarbonate and resin primers, and has excellent durability even in high temperature and high humidity environments and environments where it may come into contact with chemicals. Therefore, the active energy ray curable composition of the present invention can be suitably used as a hard coat for resin materials in automotive and building material applications, and is particularly suitable for automotive exterior and automotive glazing applications. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] <Active energy ray curable composition> The active energy ray-curable composition of the present invention (hereinafter may be simply referred to as the "composition" or "composition") contains a compound (A) (hereinafter may be referred to as the "component (A)") consisting of a chain hydrocarbon group having 2 to 12 carbon atoms and two (meth)acryloyloxy groups, and a compound having an isocyanurate bond or an allophanate bond. In this specification, the compound represented by formula (1) is referred to as "compound (1)", and the same applies to compounds represented by other formulas. In addition, "acrylate" and "methacrylate" are collectively referred to as "(meth)acrylate". Similarly, for "acrylic acid" and "methacrylic acid", "acryloyl group" and "methacryloyl group", "acryloyloxy group" (CH2=CH-CO-O-) and "methacryloyloxy group" (CH2=C(CH3)-CO-O-), the expressions "(meth)acrylic acid" and "(meth)acryloyloxy group" are explained as concepts that include both.

[0011] [Component (A)] Component (A) is a compound consisting of a chain hydrocarbon group having 2 to 12 carbon atoms and two (meth)acryloyloxy groups, and by including component (A) in the composition, the adhesion to substrates and weather resistance of the cured coating are improved. The chain hydrocarbon group having 2 to 12 carbon atoms may be linear or branched, but is preferably linear. The number of carbon atoms is preferably 4 to 10, more preferably 6 to 10. In particular, from the viewpoint of reducing skin irritation to workers during production work, 8 to 10 is preferable. Specific examples of the component (A) include (meth)acrylates having a linear hydrocarbon group, such as 1,3-propanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and 1,10-decanediol di(meth)acrylate; and (meth)acrylates having a branched hydrocarbon group, such as neopentyl glycol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 2-methyl-1,8-octanediol di(meth)acrylate, and 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate.

[0012] The component (A) may use one type of compound alone, or two or more types may be used in combination. The content of the (A) component is preferably 10 to 60% by mass, more preferably 15 to 55% by mass, and even more preferably 20 to 50% by mass, based on the total of 100% by mass of the (A) component, the compound having an isocyanurate bond or allophanate bond (specifically, one or more selected from the group consisting of a urethane (meth)acrylate compound (B) having an isocyanurate bond or allophanate bond, and a (meth)acrylate compound (C) having an isocyanurate bond), and the (D) component optionally contained (hereinafter referred to as "100% by mass of the total of the (A) to (D) components"). By setting the content to be equal to or more than the lower limit, the adhesion to the substrate and the weather resistance are further improved, and by setting the content to be equal to or less than the upper limit, the weather resistance is further improved.

[0013] [Compounds having an isocyanurate bond or an allophanate bond] The composition of the present invention contains a compound having an isocyanurate bond or an allophanate bond. The isocyanurate bond and the allophanate bond are represented by the following formulas (i) and (ii), respectively. By using a compound having an isocyanurate bond or an allophanate bond in combination with component (A), it is possible to prevent excessive erosion of the resin substrate or the resin primer by component (A), and therefore to prevent poor appearance of the coating film and deterioration of the weather resistance of the cured coating film. As long as this compound has an isocyanurate bond or an allophanate bond, there are no particular limitations on the structure other than that; however, it preferably has a polymerizable group, and more preferably has a (meth)acryloyl group ((meth)acryloyloxy group) like component (A).

[0014] [ka]

[0015] Among them, the compound having an isocyanurate bond or an allophanate bond is preferably at least one selected from the group consisting of a urethane (meth)acrylate compound (B) having an isocyanurate bond or an allophanate bond, and a (meth)acrylate compound (C) having an isocyanurate bond. Each of them will be described below.

[0016] [(B) Component] The urethane (meth)acrylate compound (B) having an isocyanurate bond or an allophanate bond (hereinafter sometimes referred to as "component (B)") is a component that contributes to the weather resistance and adhesion of the cured coating. The component (B) is not particularly limited as long as it is a compound having an isocyanurate bond or allophanate bond, a urethane bond, and a (meth)acrylate structure ((meth)acryloyl group). However, in addition to the isocyanurate bond, allophanate bond, and (meth)acryloyl group, it is also preferable that the compound has a -OC(=O)-(CH) structure. nA (nA represents an integer of 1 to 6), and a compound represented by the following formula (2) is preferred.

[0017] [ka]

[0018] In formula (2), R 21 ~R 25 each independently represents a group having a polymerizable group. R 21 ~R 25 The polymerizable group of is a (meth)acryloyl group (CH2=CR 4 -CO-(R 4 is the same as above.) is preferable, and R 21 ~R 25 A combination of a (meth)acryloyl group and a divalent linking group is preferred. R 21 ~R 25 Examples of the divalent linking group include an alkylene group having 1 to 30 carbon atoms which may have a substituent, an oxyalkylene group having 1 to 30 carbon atoms which may have a substituent, -O-, -C(=O)-O-, -OC(=O)-, -C(=O)-, -OC(=O)-O-, -C(=O)-NH-, -NH-C(=O)-, -OC(=O)-NH-, -NH-C(=O)-O-, -NH-, -C(=NH)-NH- and -NH-C(=NH)-, and combinations thereof. The hydrogen atom of the groups listed as the divalent linking group may be substituted with an alkyl group, an alkoxy group, an acyl group, etc.

[0019] n1 and n2 each independently represent 0 or 1. L 21 ~L 22each independently is a divalent linking group. L 21 ~L 22 The divalent linking group preferably has a structure in which hydroxyl groups have been removed from both ends of an alkylene diol, a caprolactone-modified diol, or polytetramethylene glycol. The alkylene diol is preferably an alkylene diol having 2 to 10 carbon atoms, and the number of repeating tetramethylene groups in polytetramethylene glycol is preferably 8 to 30. Examples of caprolactone-modified diols include "PLACCEL 205," a polycaprolactone diol with a mass average molecular weight of 530; "PLACCEL 205BA," a polycaprolactone diol with a mass average molecular weight of 530 having a carboxyl group on the side chain; "PLACCEL L205AL," a polycaprolactone diol with a mass average molecular weight of 500 that is liquid at room temperature; "PLACCEL 205H," a polycaprolactone diol with a mass average molecular weight of 530 that has improved water resistance compared to PLACCEL 205; and "PLACCEL 205H," a polycaprolactone diol with a mass average molecular weight of 530 that has improved water resistance compared to PLACCEL 205 and has a viscosity and acid value higher than PLACCEL 205. "PLACCEL 205U" is a polycaprolactone diol with a mass average molecular weight of 530, "PLACCEL 208" is a polycaprolactone diol with a mass average molecular weight of 830, "PLACCEL L208AL" is a polycaprolactone diol with a mass average molecular weight of 830 that is liquid at room temperature, "PLACCEL 210" is a polycaprolactone diol with a mass average molecular weight of 1000, "PLACCEL 210BA" is a polycaprolactone diol with a mass average molecular weight of 1000 that has a carboxyl group in the side chain, and "PLACCEL 210BA" is a polycaprolactone diol with a lower acid value and higher resistance than PLACCEL 210. "Placcel 210CP" is a polycaprolactone diol with a mass average molecular weight of 1000 with improved water resistance; "Placcel 210N" is a polycaprolactone diol with a mass average molecular weight of 1000 that has a narrower molecular weight distribution than Plaxel 210; "Placcel 212" is a polycaprolactone diol with a mass average molecular weight of 1250; "Placcel L212AL" is a polycaprolactone diol with a mass average molecular weight of 1250 that is liquid at room temperature; "Placcel 220" is a polycaprolactone diol with a mass average molecular weight of 2000; "PLACCEL 220BA" is a polycaprolactone diol having a carboxyl group and a mass average molecular weight of 2000; "PLACCEL 220CPB" is a polycaprolactone diol having a mass average molecular weight of 2000 with a lower acid value and improved water resistance compared to PLACCEL 220; "PLACCEL 220N" is a polycaprolactone diol having a mass average molecular weight of 2000 and a narrower molecular weight distribution compared to PLACCEL 220; "PLACCEL 220NP1" is a polycaprolactone diol having a mass average molecular weight of 2000 with lower crystallinity compared to PLACCEL 220;"PLACCEL L220AL" is a polycaprolactone diol with a mass average molecular weight of 2000 when liquid at room temperature, "PLACCEL 230" is a polycaprolactone diol with a mass average molecular weight of 3000 when liquid at room temperature, "PLACCEL L230AL" is a polycaprolactone diol with a mass average molecular weight of 3000 when liquid at room temperature, "PLACCEL 230CP" is a polycaprolactone diol with a mass average molecular weight of 3000 that has a lower acid value and improved water resistance compared to PLACCEL 230, and "PLACCEL 230CP" is a polycaprolactone diol with a mass average molecular weight of 4000. Examples of such polycaprolactone diols include "PLACCEL 240", "PLACCEL 240CP", a polycaprolactone diol with a mass average molecular weight of 4000 that has a lower acid value and improved water resistance compared to PLACCEL 240, "PLACCEL 220EB", a polycaprolactone diol with a mass average molecular weight of 2000 that has improved hydrolysis resistance compared to PLACCEL 220, and "PLACCEL 220EC", a polycaprolactone diol with a mass average molecular weight of 2000 that has better elastic recovery compared to PLACCEL 220EB (all trade names, manufactured by Daicel Chemical Industries, Ltd.). Of these, polycaprolactone diols having a mass average molecular weight in the range of 500 to 1500 are preferred, and those in the range of 500 to 1000 are more preferred, from the viewpoint of the weather resistance and abrasion resistance of the resulting cured coating. Furthermore, L 21 ~L 22 It is preferable that R has another linking group in addition to any one of the structures obtained by removing a hydroxyl group from the terminal of an alkylene diol, a caprolactone-modified diol, or polytetramethylene glycol. 21 ~R 25 In particular, those exemplified as "a divalent linking group possessed by the formula (I)" are preferred.

[0020] Z 21 ~Z 23 are each independently a structure represented by the following formula (2z).

[0021] [ka]

[0022] In formula (2z), X 21 is an alkylene group having 2 to 17 carbon atoms, more preferably an alkylene group having 2 to 10 carbon atoms, and further preferably an alkylene group having 2 to 6 carbon atoms.

[0023] The symbol * in formula (2z) represents a bond, and formula (2z) corresponds to Z in formula (2). 21 If B1 is R, the bond * is 21 The bond indicated by B2 is L 21 or R 22 The bond indicated by B3 is L 22 or R 23 and the formula (2z) is Z in the formula (2). 22 In this case, the bond represented by B1 is L 22 , the bond indicated by B2 is R 24 , the bond indicated by B3 is R 23 and the formula (2z) is Z in the formula (2). 23 In this case, the bond represented by B1 is L 21 , the bond indicated by B2 is R 22 , the bond indicated by B3 is R 25 directly binds to

[0024] Z 1 is an oxygen atom or a nitrogen atom, Z 2 is a hydrogen atom or -C(=O)-. 1 When is an oxygen atom (-O-), Z 2 becomes a hydrogen atom (-H). On the other hand, Z 1 If is a nitrogen atom, Z 2 becomes -C(=O)-, and Z 1 Nitrogen atom and Z 2 and -C(=O)- to form a ring. That is, Z 1 When is an oxygen atom, formula (2z) is a structure having an allophanate bond, and Z 1 When is a nitrogen atom, the formula (2z) has an isocyanurate bond. As the component (B), those having an isocyanurate bond as the formula (2z) are preferred.

[0025] Among them, the compounds represented by the following formulas (2-1) to (2-4) are preferable as compound (2).

[0026] [ka]

[0027] [ka]

[0028] [ka]

[0029] [ka]

[0030] In formulas (2-1) to (2-4), R 26 are each independently a hydrogen atom or a methyl group. In formulas (2-1) to (2-4), R 27 each independently represents an alkylene group having 2 to 10 carbon atoms (preferably, 2 to 4 carbon atoms), R A -(O-CO-(CH2)5) n - or R A -(O-(CH2)4) n -It is. R A represents an alkylene group, preferably an alkylene group having 2 to 4 carbon atoms. Each n independently represents an integer of 1 to 10, and preferably an integer of 1 to 5.

[0031] In formulas (2-1) to (2-4), X 22 are each independently an alkylene group having 2 to 17 carbon atoms, preferably an alkylene group having 2 to 10 carbon atoms, and more preferably an alkylene group having 2 to 6 carbon atoms. In the formulas (2-2) and (2-4), A1 represents a structure in which a hydroxyl group has been removed from the terminal of any one of an alkylene diol, a caprolactone-modified diol, and polytetramethylene glycol, and L 21 ~L 22 This is similar to that explained in. Multiple R in formulas (2-1) to (2-4) 26 , R 27 , X 22 may be the same or different from each other.

[0032] The component (B) may be a single compound or a combination of two or more compounds. In particular, it is preferable to use a combination of two or more compounds (B) because this can provide a good balance of various properties.

[0033] When two or more types are used, in addition to the isocyanurate bond, allophanate bond, and (meth)acryloyl group, -OC(=O)-(CH2) nA (nA represents an integer of 1 to 6), and a compound (B1) having, in addition to an isocyanurate bond, an allophanate bond, and a (meth)acryloyl group, -OC(=O)-(CH2) in the structure. nA It is preferable to use the compound (B2) which does not have (nA represents an integer of 1 to 6) in combination.

[0034] When two or more kinds are used, it is preferable that the component (B) contains the components (B11) and (B22). The component (B11) is R 27 At least one of the following is R A -(O-CO-(CH2)5) n - or R A -(O-(CH2)4) n -, or a compound in which A1 in the formula (2-2) or the formula (2-4) has a hydroxyl group removed from the end of polytetramethylene glycol or polycaprolactone diol. 27or a compound in which A1 in the formula (2-2) or (2-4) is an alkylene group, wherein a hydroxyl group has been removed from the terminal of an alkylene diol. Of these, a combination of a (B11) component represented by formula (2-1) and a (B22) component represented by formula (2-1), or a combination of a (B11) component represented by formula (2-2) in which A1 has a polycaprolactone structure and a (B22) component represented by formula (2-1) is preferred.

[0035] When the (B) component contains the (B1) and (B2) components or the (B11) and (B22) components, the content of the (B1) or (B11) component is preferably 9 to 90 mass% based on 100 mass% of the total solid content of the (A) to (C) components, more preferably 20 to 70 mass%, even more preferably 30 to 60 mass%, and particularly preferably 45 to 60 mass%. The content of the (B2) or (B22) component is preferably 5 to 60 mass%, more preferably 10 to 50 mass%, even more preferably 15 to 40 mass%, and particularly preferably 20 to 30 mass%, based on 100 mass% of the total solid content of the (A) to (C) components.

[0036] When the composition of the present invention contains component (B), the total content of component (B) is preferably 10 to 80 mass%, more preferably 15 to 70 mass%, and even more preferably 25 to 60 mass%, based on 100 mass% of the total of components (A) to (D). By making it equal to or more than the lower limit, weather resistance is improved, and by making it equal to or less than the upper limit, abrasion resistance is improved.

[0037] [(C) component] The (meth)acrylate compound (C) having an isocyanurate bond (hereinafter sometimes referred to as "component (C)") is a component that contributes to the abrasion resistance and adhesion of the cured coating. The component (C) is a compound that does not fall under the category of the above-mentioned component (B), and is a compound that does not have a urethane bond but has an isocyanurate bond and a (meth)acrylate structure ((meth)acryloyl group). Specifically, the component (C) is preferably a compound represented by the following formula (1):

[0038] [ka]

[0039] In formula (1), R 1 , R 2 and R 3 are each independently an oxyalkylene group or a polyoxyalkylene group. The oxyalkylene group preferably has 1 to 8 carbon atoms, more preferably 1 to 5 carbon atoms, and particularly preferably 1 to 3 carbon atoms. Regarding the carbon number of the polyoxyalkylene group, the number of carbon atoms per one repeating unit is preferably 1 to 8, more preferably 1 to 5, and particularly preferably 1 to 3. In addition, the number of repeating oxyalkylene groups in the polyoxyalkylene group is preferably in the range of 1 to 10. The oxygen atom of the oxyalkylene group and the terminal oxygen atom of the polyoxyalkylene group are represented by X in the formula. 1 , X 2 Or X 3 and combine.

[0040] X 1 , X 2 and X 3 are each independently CH2=CR 4 -CO-, CH2=CR 4 -CO(O(CH2)5-CO) a1 -, hydrogen atom or alkyl group, X 1 ~X 3 At least two of the following are CH2=CR 4 -CO- or CH2=CR 4 -CO(O(CH2)5-CO) a1 That is, the compound (1) is a difunctional or trifunctional (meth)acrylate. R 4 represents a hydrogen atom or a methyl group, and multiple R 4 may be the same or different, but are preferably hydrogen atoms. a1 is an integer of 1 or more, preferably an integer of 1 to 3, more preferably 1 or 2, and particularly preferably 1. Among them, X 1 , X2 and X 3 CH2=CR 4 -CO-, CH2=CR 4 -CO(O(CH2)5-CO) a1 - or a hydrogen atom is preferred, and X 1 ~X 3 At least two of the CH2=CR 4 More preferably, all three are -CO-, and all three are CH2=CR 4 It is particularly preferred that it is --CO--.

[0041] Particularly preferred examples of the compound (1) include compounds represented by the following formula (1-1). In the following formula, R 4 is the same as above, and R 1’ ~R 3’ is an alkylene group having 1 to 5 carbon atoms (preferably 1 to 3).

[0042] [ka]

[0043] Specific structures of the component (C) include bis(2-acryloyloxyethyl)hydroxylethyl isocyanurate, tris(2-acryloyloxyethyl)isocyanurate (manufactured by Toagosei Co., Ltd. under the trade names ARONIX M-313 and ARONIX M-315, manufactured by Shin-Nakamura Chemical Co., Ltd. under the trade names NK Ester A9300 and A9300S, manufactured by Arkema SR368 and SR368NS), and bis(2-acryloyloxypropyl)hydroxylethyl Examples of such isocyanurate include tris(2-acryloyloxypropyl)isocyanurate, tris(2-acryloyloxyethyl)isocyanurate modified with one caprolactone per molecule (manufactured by Toagosei Co., Ltd., product name ARONIX M-325), and tris(2-acryloyloxyethyl)isocyanurate modified with three caprolactones per molecule (manufactured by Toagosei Co., Ltd., product name ARONIX M-327).

[0044] The component (C) may be used as a single compound, or as a combination of two or more compounds. When the composition of the present invention contains component (C), the content of component (C) is preferably 1 to 79 mass%, more preferably 3 to 67.5 mass%, and even more preferably 5 to 50 mass%, based on 100 mass% of the total of components (A) to (D). By making the content equal to or more than the lower limit, the abrasion resistance and adhesion are further improved, and by making the content equal to or less than the upper limit, the weather resistance and chemical resistance are further improved.

[0045] The compound having an isocyanurate bond or an allophanate bond may be component (B), may be component (C), or may be component (B) and component (C). Among them, it is preferable to use component (B) and component (C) in combination, since the use of these in combination makes it easier to achieve improvements in weather resistance, chemical resistance, and adhesion, and to reduce appearance defects.

[0046] [(D) component] Component (D) is a compound that does not fall under the category of components (A) to (C) and contains four or more (meth)acryloyl groups in one molecule. When the composition contains component (D), the abrasion resistance and chemical resistance of the cured coating are improved. The (D) component is not particularly limited as long as it has four or more (meth)acryloyl groups in one molecule, and examples thereof include polyfunctional (meth)acrylates such as pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, tripentaerythritol octa(meth)acrylate, polypentaerythritol poly(meth)acrylate, caprolactone-modified pentaerythritol tetra(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate; and urethane (meth)acrylates obtained by reacting an isocyanate compound with a (meth)acrylate compound.

[0047] The polyfunctional (meth)acrylate as the component (D) is preferably a compound represented by the following formula (3-0).

[0048] [ka]

[0049] In formula (3-0), multiple R 30 At least four of them are CH2=CR B -COO- or (meth)acryloyloxy group CH2=CR modified with caprolactone B -CO(O(CH2)5C=O) y -O- and the remaining R 30 is a hydroxyl group, or CH2=CR B -COO-, CH2=CR 8 -CO(O(CH2)5C=O) y Represents -O-. R B represents a hydrogen atom or a methyl group, R B When R is a hydrogen atom, it becomes an acryloyl group, and R B When is a methyl group, it becomes a methacryloyl group, and y is an integer of 1 or more. That is, compound (3-0) is a polymerizable compound having a pentaerythritol skeleton and four or more (meth)acryloyloxy groups in the structure. By having four or more (meth)acryloyloxy groups, the crosslink density increases when cured, and thus abrasion resistance and chemical resistance can be improved. n30 represents an integer of 0 to 4, preferably an integer of 1 to 3, more preferably 1 or 2, and particularly preferably n30=1 so that compound (3-0) has a dipentaerythritol skeleton. The compound (3-0) may be used alone or in combination of two or more kinds.

[0050] The urethane (meth)acrylate as the component (D) can be obtained by reacting a (meth)acrylate compound having a hydroxyl group with an isocyanate compound.

[0051] The (meth)acrylate compound having a hydroxyl group used in the production of the urethane (meth)acrylate is preferably a compound represented by the following formula (3-1) or (3-2). In the following formula, R 31 ~R 32 Each independently represents a hydrogen atom or a methyl group, and multiple R 31 , R 32 may be the same or different from each other.

[0052] [ka]

[0053] The isocyanate compound used in the production of the urethane (meth)acrylate is preferably an aliphatic polyisocyanate or alicyclic polyisocyanate having two or more isocyanate groups. Specific examples of the polyisocyanate include aliphatic polyisocyanates such as 1,4-butane diisocyanate, 1,5-pentane diisocyanate, 1,6-hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, and lysine triisocyanate, and dimers or trimers thereof; and alicyclic polyisocyanates such as norbornane diisocyanate, isophorone diisocyanate, methylene bis(4-cyclohexyl isocyanate), 1,3-bis(isocyanatomethyl)cyclohexane, hydrogenated xylylene diisocyanate, 2-methyl-1,3-diisocyanatocyclohexane, and 2-methyl-1,5-diisocyanatocyclohexane, and dimers or trimers thereof.

[0054] As the isocyanate compound, a triisocyanate compound represented by the following formula (3-3) or a diisocyanate compound represented by the following formula (3-4) is also preferred.

[0055] [ka]

[0056] In the formula, X 31 ~X 32 Each of X independently represents an alkylene group having 2 to 17 carbon atoms, and preferably an alkylene group having 2 to 6 carbon atoms. 31 , X 32 may be the same or different from each other. R 33 -R C -O-CO-CH=CH2, or a structure obtained by removing a hydroxyl group from a compound represented by the formula (3-1) or (3-2), R C represents an alkylene group, and the alkylene group preferably has 1 to 30 carbon atoms, more preferably 1 to 20 carbon atoms, and particularly preferably 1 to 10 carbon atoms.

[0057] When the composition of the present invention contains component (D), the total content of component (D) is preferably 1.0 to 40 mass%, more preferably 2.5 to 20 mass%, and even more preferably 5.0 to 10 mass%, based on 100 mass% of the total of components (A) to (D). By making the content equal to or more than the lower limit, chemical resistance is improved, and by making the content equal to or less than the upper limit, weather resistance is improved.

[0058] [Other ingredients] The composition of the present invention may contain any other components in addition to the above components (A) to (D) as long as the effects of the present invention can be obtained. Examples of other components include organic solvents, reactive compounds, various resins, fillers, polymerization initiators, stabilizers, UV absorbers, and leveling agents. In addition, inorganic pigments, organic pigments, extender pigments, clay minerals, waxes, catalysts, surfactants, flow control agents, coupling agents, dyes, rheology control agents, antioxidants, plasticizers, etc. may also be contained.

[0059] The composition of the present invention may or may not contain an organic solvent. In particular, it is preferable that the composition is a solvent-free composition that does not contain an organic solvent, or a high solids composition that has a relatively low organic solvent content. By making the composition solvent-free or low-solvent / high-solids, it is possible to reduce the amount of volatile organic compounds (VOCs), thereby reducing the environmental load. When an organic solvent is contained, the content thereof is preferably 30 mass % or less of the total amount of the composition, more preferably 25 mass % or less, even more preferably 20 mass % or less, particularly preferably 15 mass % or less, and most preferably 10 mass % or less. Examples of the organic solvent include ester-based solvents, ketone-based solvents, ether-based solvents, aliphatic solvents, aromatic solvents, and alcohol-based solvents. Specifically, examples of ester solvents include ethyl acetate, propyl acetate, and butyl acetate; examples of ketone solvents include acetone, 2-butanone, methyl ethyl ketone, and methyl isobutyl ketone; examples of ether solvents include tetrahydrofuran and dioxolane; examples of aliphatic solvents include hexane and cyclohexane; examples of aromatic solvents include toluene and xylene; and examples of alcohol solvents include ethanol, methanol, propanol, butanol, and propylene glycol monomethyl ether.

[0060] As the reactive compound, a (meth)acrylate compound other than the components (A) to (D) or a compound having a double bond such as a vinyl group may be blended. As the (meth)acryloyl-based compound, there may be mentioned monofunctional (meth)acrylates and di- or trifunctional (meth)acrylates not corresponding to the components (A) to (D).

[0061] Examples of monofunctional (meth)acrylates include alkyl (meth)acrylates having an alkyl group having 1 to 22 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate; cycloalkyl (meth)acrylates, such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate; and ω-alkoxyalkyl (meth)acrylates, such as 2-methoxyethyl (meth)acrylate and 4-methoxybutyl (meth)acrylate. Examples of such hydroxyethyl (meth)acrylate include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, caprolactone-modified hydroxy(meth)acrylate (for example, trade name "Placcel" manufactured by Daicel Chemical Industries, Ltd.), polycarbonate-modified hydroxy(meth)acrylate, mono(meth)acrylate of polyester diol obtained from phthalic acid and propylene glycol, mono(meth)acrylate of polyester diol obtained from succinic acid and propylene glycol, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate, and (meth)acrylic acid adducts of various epoxy esters.

[0062] Examples of difunctional or trifunctional (meth)acrylates include dihydric alcohol di(meth)acrylates such as tricyclodecane dimethanol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and tripropylene glycol di(meth)acrylate; Polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, di(meth)acrylate of tris(2-hydroxyethyl)isocyanurate, di(meth)acrylate of diol obtained by adding 4 moles or more of ethylene oxide or propylene oxide to 1 mole of neopentyl glycol, di(meth)acrylate of diol obtained by adding 2 moles of ethylene oxide or propylene oxide to 1 mole of bisphenol A, di(meth)acrylate or tri(meth)acrylate obtained by reacting 1 mole of tris(2-hydroxyethyl)isocyanurate with 2 to 3 moles of acrylic acid, trimethylolpropane tri(meth)acrylate, polyethylene glycol di(meth)acrylate modified with ethylene oxide, polypropylene glycol di(meth)acrylate modified with propylene oxide, tetra Examples of the polytetramethylene glycol di(meth)acrylate modified with methylene oxide, glycerol tri(meth)acrylate modified with ethylene oxide, glycerol tri(meth)acrylate modified with propylene oxide, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, hydroxypivalic acid modified trimethylolpropane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate modified with ethylene oxide, trimethylolpropane tri(meth)acrylate modified with propylene oxide, phosphoric acid tri(meth)acrylate modified with ethylene oxide, polyester (meth)acrylate compounds synthesized by condensation reaction of polyhydric alcohol with (meth)acrylic acid and polyfunctional carboxylic acid, epoxy (meth)acrylate compounds synthesized by addition reaction of novolac type epoxy resin, glycidyl group-containing acrylic polymer and (meth)acrylic acid, acrylic acrylate compounds and the like.

[0063] The reactive compounds may be used alone or in combination of two or more. The amount of the reactive compound used is preferably 0 to 300% by mass relative to 100% by mass of the total amount of the solid contents of the components (A) to (D).

[0064] As the various resins, a thermosetting resin or a thermoplastic resin can be used. A thermosetting resin is a resin that has the property of becoming substantially insoluble and infusible when cured by heating, radiation, a catalyst, or other means. Specific examples of thermosetting resins include phenolic resins, urea resins, melamine resins, benzoguanamine resins, alkyd resins, unsaturated polyester resins, vinyl ester resins, diallyl terephthalate resins, epoxy resins, silicone resins, urethane resins, furan resins, ketone resins, xylene resins, thermosetting polyimide resins, benzoxazine resins, active ester resins, aniline resins, cyanate ester resins, and styrene-maleic anhydride (SMA) resins. These thermosetting resins can be used alone or in combination of two or more.

[0065] Thermoplastic resin refers to a resin that can be melt molded by heating. Specific examples thereof include polyethylene resin, polypropylene resin, polystyrene resin, rubber-modified polystyrene resin, acrylonitrile-butadiene-styrene (ABS) resin, acrylonitrile-styrene (AS) resin, polymethyl methacrylate resin, acrylic resin, polyvinyl chloride resin, polyvinylidene chloride resin, polyethylene terephthalate resin, ethylene vinyl alcohol resin, cellulose acetate resin, ionomer resin, polyacrylonitrile resin, polyamide resin, polyacetal resin, polybutylene terephthalate resin, polylactic acid resin, polyphenylene ether resin, modified polyphenylene ether resin, polycarbonate resin, polysulfone resin, polyphenylene sulfide resin, polyetherimide resin, polyethersulfone resin, polyarylate resin, thermoplastic polyimide resin, polyamideimide resin, polyetheretherketone resin, polyketone resin, liquid crystal polyester resin, fluororesin, syndiotactic polystyrene resin, and cyclic polyolefin resin. These thermoplastic resins can be used alone or in combination of two or more.

[0066] In addition, liquid organic polymers may be used to adjust viscosity. The liquid organic polymers are liquid organic polymers that do not directly contribute to the curing reaction, and examples thereof include modified carboxyl-containing polymers (Floren G-900, NC-500: Kyoeisha), acrylic polymers (Floren WK-20: Kyoeisha), amine salts of special modified phosphoric acid esters (HIPLAAD ED-251: Kusumoto Chemicals), modified acrylic block copolymers (DISPERBYK2000; BYK-Chemie), etc.

[0067] As a filler, for example, silica can be blended for the purpose of improving abrasion resistance. The silica is not limited, and known silica particles such as powdered silica, colloidal silica, nanosilica, etc. can be used. Examples of commercially available powdered silica particles include Aerosil 50 and 200 manufactured by Nippon Aerosil Co., Ltd., Sildex H31, H32, H51, H52, H121, and H122 manufactured by Asahi Glass Co., Ltd., E220A and E220 manufactured by Nippon Silica Industry Co., Ltd., SYLYSIA470 manufactured by Fuji Silysia Co., Ltd., and SG Flake manufactured by Nippon Sheet Glass Co., Ltd. Examples of commercially available colloidal silica include methanol silica sol, IPA-ST, MEK-ST, PGM-ST, NBA-ST, XBA-ST, DMAC-ST, ST-UP, ST-OUP, ST-20, ST-40, ST-C, ST-N, ST-O, ST-50, and ST-OL, all of which are manufactured by Nissan Chemical Industries, Ltd.

[0068] Silica may be reactive silica. Reactive silica may be, for example, reactive compound modified silica. Reactive compounds may be, for example, reactive silane coupling agents having hydrophobic groups, compounds having (meth)acryloyl groups, compounds having maleimide groups, and compounds having glycidyl groups. Examples of commercially available powdered silica modified with a compound having a (meth)acryloyl group include Aerosil RM50 and R711 manufactured by Nippon Aerosil Co., Ltd., and examples of commercially available colloidal silica modified with a compound having a (meth)acryloyl group include MIBK-SD, MIBK-SD-L, MIBK-AC-2140Z, MEK-AC-2140Z, and the like manufactured by Nissan Chemical Industries, Ltd. Examples of reactive silica include silica modified with a glycidyl group such as 3-glycidoxypropyltrimethoxysilane and then subjected to an addition reaction with acrylic acid, and silica modified with a compound having a urethane reaction of 3-isocyanatepropyltriethoxysilane, a hydroxyl group, and a (meth)acryloyl group.

[0069] The shape of the silica fine particles is not particularly limited, and spherical, hollow, porous, rod-like, plate-like, fibrous, or amorphous silica fine particles can be used. For example, commercially available hollow silica fine particles such as Silinax manufactured by Nittetsu Mining Co., Ltd. can be used. The primary particle size is preferably in the range of 5 to 200 nm. If it is 5 nm or more, the inorganic fine particles are sufficiently dispersed in the composition, and if it is 200 nm or less, the cured product can maintain sufficient strength. The blending amount of silica is preferably 3 to 60 mass % in 100 mass % of the composition.

[0070] Fillers other than silica include inorganic fillers and organic fillers. There is no limitation on the shape of the filler, and examples of the filler include particulate, plate-like, and fibrous fillers. Examples of fillers with excellent heat resistance include alumina, magnesia, titania, zirconia, etc.; examples of fillers with excellent thermal conductivity include boron nitride, aluminum nitride, alumina oxide, titanium oxide, magnesium oxide, zinc oxide, silicon oxide, etc.; examples of fillers with excellent electrical conductivity include metal fillers and / or metal-coated fillers using metals or alloys (e.g., iron, copper, magnesium, aluminum, gold, silver, platinum, zinc, manganese, stainless steel, etc.); examples of fillers with excellent barrier properties include minerals such as mica, clay, kaolin, talc, zeolite, wollastonite, and smectite, potassium titanate, magnesium sulfate, sepiolite, zonolite, aluminum borate, calcium carbonate, titanium oxide, etc. those with a high refractive index include barium titanate, zirconia oxide, titanium oxide, etc.; those exhibiting photocatalytic properties include photocatalytic metals such as titanium, cerium, zinc, copper, aluminum, tin, indium, phosphorus, carbon, sulfur, cerium, nickel, iron, cobalt, silver, molybdenum, strontium, chromium, barium, lead, etc., composites of these metals, and oxides thereof; those with excellent abrasion resistance include metals such as alumina, zirconia, magnesium oxide, etc., and composites and oxides thereof; those with excellent electrical conductivity include metals such as silver and copper, tin oxide, indium oxide, etc.; and those with excellent ultraviolet ray shielding properties include titanium oxide, zinc oxide, etc. These inorganic fine particles may be selected according to the intended use, and may be used alone or in combination of two or more kinds. In addition, the inorganic fine particles have various properties other than those exemplified, so that they may be selected according to the intended use.

[0071] Examples of inorganic fibers include inorganic fibers such as carbon fibers, glass fibers, boron fibers, alumina fibers, and silicon carbide fibers, as well as carbon fibers, activated carbon fibers, graphite fibers, glass fibers, tungsten carbide fibers, silicon carbide fibers (silicon carbide fibers), ceramic fibers, alumina fibers, natural fibers, mineral fibers such as basalt, boron fibers, boron nitride fibers, boron carbide fibers, and metal fibers. Examples of the metal fibers include aluminum fibers, copper fibers, brass fibers, stainless steel fibers, and steel fibers.

[0072] Examples of organic fibers include synthetic fibers made of resin materials such as polybenzazole, aramid, PBO (polyparaphenylene benzoxazole), polyphenylene sulfide, polyester, acrylic, polyamide, polyolefin, polyvinyl alcohol, and polyarylate; natural fibers such as cellulose, pulp, cotton, wool, and silk; and regenerated fibers such as protein, polypeptide, and alginic acid.

[0073] The amount of the filler to be blended is preferably 3 to 60% by mass in 100% by mass of the composition.

[0074] Since the composition of the present invention is cured by active energy rays, it is preferable to use a polymerization initiator, particularly a photopolymerization initiator. As the photopolymerization initiator, any known initiator may be used, and for example, one or more selected from the group consisting of acetophenones, benzil ketals, and benzophenones can be preferably used.

[0075] Specific examples of photoinitiated polymerization initiators include 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxycyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, dienes, acetophenone compounds such as oligo{2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone} and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methyl-propan-1-one; benzophenone compounds such as benzophenone, 4-phenylbenzophenone, 2,4,6-trimethylbenzophenone and 4-benzoyl-4'-methyl-diphenyl sulfide; methylbenzoyl formate, oxypheny α-Ketoester compounds such as 2-(2-oxo-2-phenylacetoxyethoxy)ethyl ester of phenylacetic acid and 2-(2-hydroxyethoxy)ethyl ester of oxyphenylacetic acid; phosphine oxide compounds such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide; benzoin, benzoin methyl ether ... benzoin-based compounds such as benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; titanocene-based compounds; acetophenone / benzophenone hybrid photopolymerization initiators such as 1-[4-(4-benzoylphenylsulfanyl)phenyl]-2-methyl-2-(4-methylphenylsulfinyl)propan-1-one; oxime ester photopolymerization initiators such as 2-(O-benzoyloxime)-1-[4-(phenylthio)]-1,2-octanedione; and camphorquinone.

[0076] The photopolymerization initiator may be used alone or in combination of two or more kinds. The amount of the photopolymerization initiator used is preferably 1 to 15% by mass, more preferably 2 to 10% by mass, based on 100% by mass of the composition.

[0077] The composition of the present invention may contain an ultraviolet absorbing agent for the purpose of improving weather resistance. As the ultraviolet absorbing agent, various compounds or substances can be used. Specific examples of ultraviolet absorbers include 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxy-phenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxy-phenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-(2-ethylhexyloxy)propyl]oxy]-2-hydroxy-phenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, benzotriazine-based ultraviolet absorbers such as 2,4-bis(2-hydroxy-4-butyloxyphenyl)-6-(2,4-bis-butyloxyphenyl)-1,3,5-triazine, and 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine; Benzotriazole-based ultraviolet absorbers such as 2-(2H-benzotriazole-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole, and 2-[2-hydroxy-5-(2-(meth)acryloyloxyethyl)phenyl]-2H-benzotriazole; benzophenone-based ultraviolet absorbers such as 2,4-dihydroxybenzophenone and 2-hydroxy-4-methoxybenzophenone; cyanoacrylate-based ultraviolet absorbers such as ethyl-2-cyano-3,3-diphenylacrylate and octyl-2-cyano-3,3-diphenylacrylate; and inorganic fine particles that absorb ultraviolet light such as titanium oxide fine particles, zinc oxide fine particles, and tin oxide fine particles. The ultraviolet absorbers listed above may be used alone or in combination of two or more.

[0078] The ultraviolet absorber may be a commercially available product. Examples of commercially available products include TINUVIN PS, TINUVIN 99-2, TINUVIN 234, TINUVIN 326, TINUVIN 329, TINUVIN 900, TINUVIN 928, TINUVIN 360, TINUVIN 384-2, TINUVIN 400, TINUVIN 405, TINUVIN 460, TINUVIN 477, and TINUVIN 479 (all manufactured by BASF); Adeka STAB LA-46, Adeka STAB LA-F70, Adeka STAB LA-29, Adeka STAB LA-31G, Adeka STAB LA-32, and Adeka STAB LA-36 (all manufactured by ADEKA); and RUVA-93 (manufactured by Otsuka Chemical Co., Ltd.).

[0079] From the viewpoint of improving weather resistance, benzotriazine type ultraviolet absorbers or ultraviolet absorbers having a (meth)acryloyl group are preferred. Preferred are TINUVIN 400, TINUVIN 405, TINUVIN 479 (all manufactured by BASF), Adeka STAB LA-46 (manufactured by ADEKA), and RUVA-93 (manufactured by Otsuka Chemical).

[0080] The amount of the ultraviolet absorber used is preferably from 0.5 to 20% by mass, and more preferably from 1 to 10% by mass, based on 100% by mass of the composition.

[0081] The composition of the present invention may contain a hindered amine light stabilizer (HALS) for the purpose of improving weather resistance. As the hindered amine-based light stabilizer, known hindered amine-based light stabilizers can be used. Specifically, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, bis(1-methoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-ethoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-propoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1 -butoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-pentyloxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-hexyloxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-heptyloxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-nonyloxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate bis(1-decyloxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1-dodecyloxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)-2-(4-methoxybenzylidene)malonate, tetrakis(2,2,6,6-pentamethyl-4-piperidyl) 1,2,3,4-butanetetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl) 1,2,3,4-butanetetracarboxylate tetracarboxylate, a condensation product of 1,2,3,4-butanetetracarboxylic acid, 1,2,2,6,6-pentamethyl-4-piperidinol, and β,β,β,β-tetramethyl-3,9-(2,4,8,10-tetraoxaspiro[5,5])undecane)diethanol, and a condensation product of 1,2,3,4-butanetetracarboxylic acid, 2,2,6,6-pentamethyl-4-piperidinol, and β,β,β,β-tetramethyl-3,9-(2,4,8,10-tetraoxaspiro[5,5])undecane)diethanol.

[0082] Commercially available hindered amine light stabilizers can also be used. Commercially available products include TINUVIN123, TINUVIN292, TINUVIN152, TINUVIN144, TINUVIN622SF), TINUVIN111FDL, TINUVIN249, and Adeka STAB LA-52 (all manufactured by BASF); Adeka STAB LA-57, Adeka STAB LA-63P, Adeka STAB LA-68, Adeka STAB LA-72, Adeka STAB LA-81, Adeka STAB LA-82, and Adeka STAB LA-87 (all manufactured by ADEKA).

[0083] From the viewpoint of improving weather resistance, TINUVIN123, TINUVIN152, TINUVIN144 (all manufactured by BASF), Adeka STAB LA-52, Adeka STAB LA-57, Adeka STAB LA-63P, Adeka STAB LA-68, Adeka STAB LA-72, Adeka STAB LA-81 (manufactured by ADEKA), Adeka STAB LA-82 (manufactured by ADEKA), and Adeka STAB LA-87 (manufactured by ADEKA) are preferred. More preferred are TINUVIN123, TINUVIN152 (all manufactured by BASF), Adeka STAB LA-63P, Adeka STAB LA-82 (manufactured by ADEKA), and Adeka STAB LA-87 (manufactured by ADEKA).

[0084] The amount of the hindered amine light stabilizer used is preferably from 0.01 to 10% by mass, and more preferably from 0.1 to 5% by mass, based on 100% by mass of the composition.

[0085] Various surface modifiers may be added to the composition of the present invention for the purpose of improving the leveling property during application, or for the purpose of improving the slipperiness of the cured film to improve the scratch resistance. As the surface modifier, various additives that modify the surface properties and are commercially available under the names of surface conditioners, leveling agents, slipperiness imparting agents, antifouling agents, etc. can be used. Among them, silicone-based surface modifiers and fluorine-based surface modifiers are preferred. Specifically, silicone-based polymers and oligomers having a silicone chain and a polyalkylene oxide chain, silicone-based polymers and oligomers having a silicone chain and a polyester chain, fluorine-based polymers and oligomers having a perfluoroalkyl group and a polyalkylene oxide chain, fluorine-based polymers and oligomers having a perfluoroalkyl ether chain and a polyalkylene oxide chain, etc. may be used. At least one of these may be used. For the purpose of increasing the durability of the slipperiness, one containing a (meth)acryloyl group in the molecule may be used. Specific surface modifiers include EBECRYL350 (Daicel-Allnex Co., Ltd.), BYK-333 (BYK Japan Co., Ltd.), BYK-377 (BYK Japan Co., Ltd.), BYK-378 (BYK Japan Co., Ltd.), BYK-UV3500 (BYK Japan Co., Ltd.), BYK-UV3505 (BYK Japan Co., Ltd.), BYK-UV3576 (BYK Japan Co., Ltd.), Megafac RS-75 (DIC Corporation), Megafac RS-76-E (DIC Corporation), Megafac RS-72-K (DIC Corporation), Megafac RS-76-NS (DIC Corporation), Megafac RS-90 (DIC Corporation), Megafac RS-91 (DIC Corporation), Megafac RS-55 (DIC Corporation), Optool DAC-HP (Daikin Industries, Ltd.), ZX-058-A (T&K Corporation), Examples of the ZX-22-164A (Shin-Etsu Chemical Co., Ltd.), X-22-164B (Shin-Etsu Chemical Co., Ltd.), X-22-164C (Shin-Etsu Chemical Co., Ltd.), X-22-164E (Shin-Etsu Chemical Co., Ltd.), and X-22-174DX (Shin-Etsu Chemical Co., Ltd.) can be mentioned.

[0086] The active energy ray curable composition of the present invention can be suitably used as a cured coating film for protecting a substrate by applying it to at least one surface of various materials and then irradiating it with active energy rays. The cured coating film made of the composition of the present invention has weather resistance and abrasion resistance, high chemical resistance, and excellent adhesion to various materials even under harsh environments such as high temperature and high humidity, so it exerts excellent effects when used as a protective coating film for materials used for a long period of time under harsh environments such as outdoors and around automobiles. In addition, since the active energy ray curable composition of the present invention has a moderate substrate erosion property and therefore has particularly excellent adhesion to the substrate, a coating with high adhesion can be formed on a coating formed by partially or completely curing the active energy ray curable composition. Therefore, when the thickness of the cured coating is not sufficient by one application and curing, a thick cured coating with excellent durability can be formed by repeating the application and curing.

[0087] <Laminate> The laminate of the present invention has a cured layer of the above-mentioned active energy ray curable composition. The laminate may have one or more other layers in addition to the cured layer, and the other layers may include, for example, a substrate layer. The manufacturing methods of the substrate and the laminate will be described later.

[0088] <Method of manufacturing laminate> The method for producing a laminate of the present invention includes step 1 of applying the above-mentioned active energy ray-curable composition onto a substrate to obtain a coating film, and step 2 of irradiating the coating film with active energy rays to cure a part or all of the coating film.

[0089] (Process 1) In step 1, the above-mentioned active energy ray-curable composition is applied onto a substrate to obtain a coating film. The substrate is not particularly limited and may be appropriately selected depending on the application.Specific examples include plastic, wood, metal (steel, stainless steel, aluminum, etc.), metal oxide, paper, silicon, modified silicon, etc., and may be a substrate obtained by bonding different materials, or a substrate on which the active energy ray curable composition of the present invention or another composition is laminated as a primer. In particular, the active energy ray curable composition of the present invention has excellent adhesion to plastic substrates (resin substrates) and resin primers. As described above, resin materials have defects such as low abrasion resistance, which easily causes loss of gloss and transparency, and poor weather resistance, but these defects can be improved by coating the plastic substrate or resin primer with the composition of the present invention. Therefore, plastic substrates and resin primers are preferred as substrates for laminates.

[0090] The plastic substrate is not particularly limited as long as it is made of resin, and can be selected according to the purpose. Specifically, the above-mentioned thermosetting resin or thermoplastic resin can be used. In the case of obtaining a transparent laminate, polycarbonate resin (e.g., aliphatic polycarbonate, aromatic polycarbonate, alicyclic polycarbonate, etc.), polymethyl methacrylate resin, polystyrene resin, etc. are preferably used. The plastic substrate may be made of a single resin or a mixture of multiple resins, and may be a single layer or may already have a laminated structure of two or more layers. In addition, the plastic substrate may contain known additives such as known antistatic agents, antifogging agents, antiblocking agents, ultraviolet absorbers, antioxidants, pigments, organic fillers, inorganic fillers, light stabilizers, crystal nucleating agents, and lubricants, and may be fiber-reinforced plastic (FRP).

[0091] As the resin primer, known water-soluble or water-dispersed paints, organic solvent-based or organic solvent-dispersed paints, powder paints, etc. can be used. Specifically, various types of paints such as acrylic resin-based paints, polyester resin-based paints, alkyd resin-based paints, epoxy resin-based paints, fatty acid-modified epoxy resin-based paints, silicon resin-based paints, polyurethane resin-based paints, fluoroolefin-based paints, or amine-modified epoxy resin paints can be used. The undercoat paint may be a clear paint that does not contain a pigment, an enamel-based paint that contains the pigment, or a metallic paint that contains aluminum flakes, or it may be a paint used for electrodeposition paints, midcoat paints, topcoat paints, or precoat metals used on automobile bodies.

[0092] The shape of the substrate is not particularly limited, and may be any shape according to the purpose, such as a flat plate, a sheet, or a three-dimensional shape having a curvature (bend) entirely or partially. Furthermore, the hardness, thickness, etc. of the substrate are not particularly limited and can be determined arbitrarily.

[0093] The method of applying the composition is not particularly limited, and may be an inkjet method, a spray method, a spin coating method, a dip method, a roll coating method, a blade coating method, a doctor roll method, a doctor blade method, a curtain coating method, a slit coating method, a screen printing method, or the like. By applying the composition to a substrate by these methods, a coating film is obtained. In addition, when the composition is recoated after curing, the inkjet method and the spray method are preferred from the viewpoint of the coating method.

[0094] (Process 2) In step 2, the coating film obtained in step 1 is irradiated with active energy rays to cure a part or the whole of the coating film. Since the composition of the present invention contains a compound having a polymerizable unsaturated group, it can be cured by irradiating with active energy rays to form a cured coating (cured layer). The entire coating film may be cured by one irradiation to form a cured coating, or only a part of the coating film may be cured by irradiation, and then the degree of curing may be gradually increased by multiple irradiations to finally form a cured coating. In addition, between multiple irradiations, an active energy ray curable composition may be further applied from above.

[0095] Examples of active energy rays include ultraviolet rays, electron beams, α rays, β rays, γ rays, and other ionizing radiation. Among these, ultraviolet rays (UV) are preferred from the standpoint of curability and convenience. Here, when ultraviolet rays are used as the active energy rays, examples of the device for irradiating the ultraviolet rays include low pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, metal halide lamps, electrodeless lamps (fusion lamps), chemical lamps, black light lamps, mercury-xenon lamps, short arc lamps, helium-cadmium lasers, argon lasers, sunlight, LED lamps, etc. Using these, it is possible to obtain a cured coating or a cured product by irradiating the coated or molded composition with ultraviolet rays having a wavelength of about 180 to 400 nm. The amount of ultraviolet irradiation is appropriately selected depending on the type and amount of the photopolymerization initiator used.

[0096] After completion of step 2, steps 1 and 2 may be repeated in this order at least once. By repeating step 1 (application) and step 2 (curing), the cured coating can be made thicker. This method is useful when the thickness of the cured coating is insufficient after one application and curing due to a balance between the application method and the required coating thickness. The composition of the present invention has an appropriate degree of substrate erosion, and therefore adhesion is not impaired even when a cured coating is formed on the coating made of the cured composition. To further improve adhesion, the coating film can be left partially cured (semi-cured) rather than completely cured in step 2. Leaving some parts uncured improves adhesion to the lower layer. When only part of the coating film is cured, it is possible to adjust the degree of curing by adjusting the amount of active energy rays irradiated.

[0097] The laminate of the present invention may further have a second substrate on the substrate and the cured layer. The material of the second substrate is not particularly limited, and examples thereof include wood, metal, metal oxide, plastic, paper, silicon, or modified silicon, and may be a substrate obtained by bonding different materials. The shape of the substrate is not particularly limited, and may be any shape according to the purpose, such as a flat plate, a sheet, or a three-dimensional shape having a curvature on the entire surface or part. In addition, there is no limitation on the hardness, thickness, etc. of the substrate.

[0098] The laminate of the present invention can be preferably used as an interlayer material between different materials because the cured layer has high adhesion to both plastics and inorganic materials. Particularly preferably, the substrate is a plastic and the second substrate is an inorganic layer. Examples of inorganic layers include quartz, sapphire, glass, optical films, ceramic materials, inorganic oxides, vapor deposition films (CVD, PVD, sputtering), magnetic films, reflective films, metals such as Ni, Cu, Cr, Fe, and stainless steel, paper, plastic layers such as SOG (Spin On Glass), SOC (Spin On Carbon), polyester, polycarbonate, and polyimide, TFT array substrates, electrode plates for PDPs, conductive substrates such as ITO and metals, insulating substrates, silicon-based substrates such as silicon, silicon nitride, polysilicon, silicon oxide, and amorphous silicon.

[0099] In addition, the cured layer of the present invention has excellent processability even after the active energy ray curable composition is cured to form a cured layer, so it can be bent together with the substrate. For example, after the composition is directly applied to a flat substrate to obtain a substrate after coating, the coating is irradiated with active energy rays to form a substrate with a cured coating (i.e., a laminate), and the substrate can be bent. Therefore, there is no need to take care when applying the composition to a curved substrate, and the productivity of the bending material can be significantly improved. In addition, the molded product of the present invention not only has excellent bending properties under heating, but also has excellent hard coat properties after hot bending. When bending is performed, the thickness of the coating film obtained by applying the composition of the present invention is preferably 0.5 to 40 μm, more preferably 3 to 35 μm, even more preferably 5 to 30 μm, and particularly preferably 10 to 25 μm. By making the thickness equal to or more than the above lower limit, abrasion resistance and weather resistance are sufficiently exhibited, and by making the thickness equal to or less than the above upper limit, bending property can be improved.

[0100] The bending method is not particularly limited, and in addition to bending in which the laminate is directly bent, processing methods such as press molding, free blow molding, vacuum molding, pressure molding, and twin composite molding can be mentioned. The hot bending temperature is preferably 80° C. or higher, and more preferably 150° C. or higher. The upper limit temperature can be appropriately set below the melting temperature of the base material.

[0101] The laminate of the present application is excellent in weather resistance, abrasion resistance, chemical resistance, adhesion and appearance, and therefore can be particularly suitably used as various protective materials. For example, it can be used for building materials, housing equipment, transportation equipment such as automobiles, ships, aircraft and railways, electronic materials, recording materials, optical materials, lighting, packaging materials, protection of outdoor installations, optical fiber coating, resin glass protection, etc., and can be particularly suitably used for automobile headlamp lenses, automobile glazing, automobile body exteriors, plastic building materials, and steel sheets for building materials. EXAMPLES

[0102] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following aspects. In the examples, "parts" and "%" are by weight unless otherwise specified.

[0103] (Synthesis Example 1: Synthesis of UA-1) In a 1-liter flask equipped with a stirrer, a gas inlet tube, a condenser, and a thermometer, BASF's "Basonat (registered trademark) HA 3000" (NCO equivalent 19.5% by mass, 213.39 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.91 parts by mass), methoxyhydroquinone (0.09 parts by mass), and dibutyltin diacetate (0.09 parts by mass) were added, heated to 70°C, and 2-hydroxyethyl acrylate (116.1 parts by mass) was charged in portions over 1 hour. After charging, the 2250 cm -1 The reaction was continued at 80° C. until the infrared absorption spectrum of the compound disappeared, to obtain a urethane (meth)acrylate compound UA-1 having an allophanate bond.

[0104] (Synthesis Example 2: Synthesis of UA-2) In a 1-liter flask equipped with a stirrer, a gas inlet tube, a condenser, and a thermometer, BASF's "Basonat (registered trademark) HA 3000" (NCO equivalent 19.5% by mass, 213.39 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.72 parts by mass), methoxyhydroquinone (0.07 parts by mass), and dibutyltin diacetate (0.07 parts by mass) were added, heated to 70°C, and 4-hydroxybutyl acrylate (144.2 parts by mass) was charged in portions over 1 hour. After charging, the 2250 cm -1 The reaction was continued at 80° C. until the infrared absorption spectrum of the compound disappeared, thereby obtaining a urethane (meth)acrylate compound UA-2 having an allophanate bond.

[0105] (Synthesis Example 3: Synthesis of UA-3) A 1-liter flask equipped with a stirrer, a gas inlet tube, a condenser, and a thermometer was charged with BASF's "Basonat (registered trademark) HA 3000" (NCO equivalent 19.5% by mass, 213.39 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.91 parts by mass), methoxyhydroquinone (0.09 parts by mass), and dibutyltin diacetate (0.09 parts by mass), and the temperature was raised to 70 ° C., and 2-hydroxyethyl acrylate (77.4 parts by mass) and Daicel's "Placcel-210" (hydroxyl value: 113.4 164.90 parts by mass) were charged in portions over 1 hour. After charging, the 2250 cm indicating the isocyanate group was -1 The reaction was continued at 80° C. until the infrared absorption spectrum of the compound disappeared, to obtain a urethane (meth)acrylate compound UA-3 having an allophanate bond.

[0106] (Synthesis Example 4: Synthesis of UA-4) In a 1-liter flask equipped with a stirrer, a gas inlet tube, a condenser, and a thermometer, BASF's "Basonat (registered trademark) HA 3000" (NCO equivalent 19.5% by mass, 213.39 parts by mass), 2,6-di-tert-butyl-4-methylphenol (1.12 parts by mass), methoxyhydroquinone (0.11 parts by mass), and dibutyltin diacetate (0.11 parts by mass) were added, heated to 70°C, and PLAXEL FA-2D (344.0 parts by mass) was charged in portions over 1 hour. After charging, the 2250 cm -1 The reaction was continued at 80° C. until the infrared absorption spectrum of the compound disappeared, to obtain a urethane (meth)acrylate compound UA-4 having an allophanate bond.

[0107] (Synthesis Example 5: Synthesis of UA-5) In a 1-liter flask equipped with a stirrer, a gas inlet tube, a condenser, and a thermometer, DIC's Burnock DN-902S (NCO equivalent 23.5% by mass, 178.72 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.84 parts by mass), methoxyhydroquinone (0.084 parts by mass), and dibutyltin diacetate (0.084 parts by mass) were added, heated to 70°C, and 2-hydroxyethyl acrylate (116.1 parts by mass) was added in portions over 1 hour. After the addition, the 2250 cm -1 The reaction was continued at 80° C. until the infrared absorption spectrum of the above disappeared, to obtain a urethane (meth)acrylate compound UA-5 having an isocyanurate bond.

[0108] (Synthesis Example 6: Synthesis of UA-6) In a 1-liter flask equipped with a stirrer, a gas inlet tube, a condenser, and a thermometer, DIC's "Burnoc DN-902S" (NCO equivalent 23.5% by mass, 178.72 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.65 parts by mass), methoxyhydroquinone (0.07 parts by mass), and dibutyltin diacetate (0.07 parts by mass) were added, heated to 70°C, and 4-hydroxybutyl acrylate (144.2 parts by mass) was added in portions over 1 hour. After the addition, the 2250 cm -1 The reaction was continued at 80° C. until the infrared absorption spectrum of the compound disappeared, thereby obtaining a urethane (meth)acrylate compound UA-6 having an isocyanurate bond.

[0109] (Synthesis Example 7: Synthesis of UA-7) In a 1-liter flask equipped with a stirrer, a gas inlet tube, a condenser, and a thermometer, DIC Corporation's "Burnoock DN-902S" (NCO equivalent 23.5% by mass, 178.72 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.84 parts by mass), methoxyhydroquinone (0.084 parts by mass), and dibutyltin diacetate (0.084 parts by mass) were added, and the temperature was raised to 70°C. 2-hydroxyethyl acrylate (77.4 parts by mass) and Daicel Corporation's "Placcel-210" (hydroxyl value: 113.4 164.90 parts by mass) were charged in portions over 1 hour. After charging, the 2250 cm -1 The reaction was continued at 80° C. until the infrared absorption spectrum of the compound disappeared, thereby obtaining a urethane (meth)acrylate compound UA-7 having an isocyanurate bond.

[0110] (Synthesis Example 8: Synthesis of UA-8) Into a 1-liter flask equipped with a stirrer, a gas inlet tube, a condenser, and a thermometer, DIC's "Burnoock DN-902S" (NCO equivalent 23.5% by mass, 178.72 parts by mass), 2,6-di-tert-butyl-4-methylphenol (1.05 parts by mass), methoxyhydroquinone (0.11 parts by mass), and dibutyltin diacetate (0.11 parts by mass) were added, heated to 70°C, and Plaxel FA-2D (344.0 parts by mass) was charged in portions over a period of 1 hour. After the charging, the 2250 cm -1 The reaction was continued at 80° C. until the infrared absorption spectrum of the above disappeared, to obtain a urethane (meth)acrylate compound UA-8 having an isocyanurate bond.

[0111] (Synthesis Example 9: Synthesis of UA-9) In a 1-liter flask equipped with a stirrer, a gas inlet tube, a condenser, and a thermometer, "Desmodur I" (NCO equivalent 37.8% by mass, 111.15 parts by mass) manufactured by Sumika Covestro Urethane Co., Ltd., 2,6-di-tert-butyl-4-methylphenol (0.84 parts by mass), methoxyhydroquinone (0.084 parts by mass), and dibutyltin diacetate (0.084 parts by mass) were added, heated to 70°C, and 2-hydroxyethyl acrylate (116.1 parts by mass) was added in portions over 1 hour. After the addition, the 2250 cm -1 The reaction was continued at 80° C. until the infrared absorption spectrum of the above disappeared, to obtain a urethane (meth)acrylate compound UA-9 having an isocyanurate bond.

[0112] (Synthesis Example 10: Synthesis of UA-10) In a 1-liter flask equipped with a stirrer, a gas inlet tube, a condenser, and a thermometer, "Desmodur I" manufactured by Sumika Covestro Urethane Co., Ltd. (NCO equivalent: 37.8% by mass, 111.15 parts by mass), 2,6-di-tert-butyl-4-methylphenol (0.84 parts by mass), methoxyhydroquinone (0.084 parts by mass), and dibutyltin diacetate (0.084 parts by mass) were added, and the temperature was raised to 70°C. 2-hydroxyethyl acrylate (116.1 parts by mass) and "Placcel-210" manufactured by Daicel Corporation (hydroxyl value: 113.4, 247.35 parts by mass) were charged in portions over a period of 1 hour. After the charging, the 2250 cm -1 The reaction was continued at 80° C. until the infrared absorption spectrum of the compound disappeared, thereby obtaining a urethane (meth)acrylate compound UA-10 having an isocyanurate bond.

[0113] (Synthesis Example 11: Synthesis of UA-11) In a 1-liter flask equipped with a stirrer, a gas inlet tube, a condenser, and a thermometer, Covestro's "Desmodur H" (84.10 parts by mass), 2,6-di-tert-butyl-4-methylphenol (1.39 parts by mass), methoxyhydroquinone (0.14 parts by mass), and dibutyltin diacetate (0.14 parts by mass) were added, and the mixture was heated to 70°C, and Toa Gosei's "Aronix M-403 (hydroxyl value 92)" (609.78 parts by mass) was charged in portions over 1 hour. After charging, the reaction was carried out at 80°C until the infrared absorption spectrum at 2250 cm-1 indicating an isocyanate group disappeared, and a tetrafunctional or higher (meth)acrylate compound UA-11 was obtained.

[0114] (Synthesis Example 12: Synthesis of UA-12) In a 1-liter flask equipped with a stirrer, a gas inlet tube, a condenser, and a thermometer, DIC's Burnock DN-902S (178.72 parts by mass), 2,6-di-tert-butyl-4-methylphenol (1.01 parts by mass), methoxyhydroquinone (0.10 parts by mass), and dibutyltin diacetate (0.10 parts by mass) were added, heated to 70°C, and Toagosei's Aronix M-306 (hydroxyl value 157.2) (356.87 parts by mass) was added in portions over a period of 1 hour. After the addition, the 2250 cm -1 The reaction was continued at 80° C. until the infrared absorption spectrum of the compound disappeared, thereby obtaining a tetrafunctional or higher (meth)acrylate compound UA-12.

[0115] Example 1 10 parts by mass of 1,4-butanediol diacrylate as the (A) component, 10 parts by mass of UA-1 as the (B2) component, 80 parts by mass of tris-(2-acryloxyethyl)isocyanurate as the (C) component, 1.5 parts by mass of Omunirad754 (manufactured by IGM) and 1.5 parts by mass of Omunirad819 (manufactured by IGM) as photopolymerization initiators, 0.25 parts by mass of Tinuvin123 (manufactured by BASF) as HALS, and 4 parts by mass of RUVA-93 (manufactured by Otsuka Chemical Co., Ltd.) as an ultraviolet absorber were uniformly mixed in a mixed organic solvent of propylene glycol monomethyl ether / butyl acetate = 50 / 50 mass% to a solid content of 70 mass%, to prepare an active energy ray curable composition of Example 1.

[0116] (Examples 2 to 44, Comparative Examples 1 to 5) The active energy ray-curable compositions of each example were obtained in the same manner as in Example 1, except that the compositions and solid content ratios were changed as shown in Tables 1 to 6. Note that, although the photopolymerization initiator and the organic solvent type are not described in the tables, they were used in all examples in the same manner as in Example 1.

[0117] [Preparation of evaluation samples] The active energy ray-curable composition of each example was applied to a substrate shown in Tables 1 to 6 using a bar coater, dried at 80°C for 4 minutes, and then exposed to an ultraviolet ray irradiation device (GS-YUASA, high-pressure mercury lamp) under atmospheric pressure at an illuminance of 200 mW / cm. 2 , irradiation light amount 1000mJ / cm 2 A laminate having a cured coating film with a thickness of 20 μm was obtained.

[0118] [Appearance evaluation] The appearance of the evaluation sample of each example after curing was visually observed and rated according to the following criteria, with a grade of B or higher being considered to be acceptable. The results are shown in Tables 1 to 6 as "appearance". A: No defects in appearance B: The unevenness of the base or scratches on the base during painting are slightly visible C: Partially bleached D: Completely bleached

[0119] [Chemical resistance evaluation] A spot test was carried out on the evaluation sample of each example by a drop test using a 40% by mass aqueous solution of sulfuric acid in accordance with JIS K 5600-6. The maximum time during which no defects in the appearance of the cured coating were observed was regarded as the evaluation result. 15 minutes or more was regarded as a pass, and if no defects in appearance were observed for more than 50 minutes until the end of the test, it was rated as "50". The resulting time (unit: minutes) is shown in Tables 1 to 6 as "chemical resistance".

[0120] [Weather resistance rating: A] An accelerated weathering test (SUV test) was performed on the evaluation samples of each example using the following conditions: Conditions: Irradiation (63℃・90%RH・100mW / cm 2 4 hours) → darkness (70℃ 90% RH 4 hours) → condensation (30℃, 98% RH 4 hours), with shower before and after irradiation. The appearance was visually checked every cycle (96 hours), and the maximum number of cycles in which no cracks were observed in the cured coating was regarded as the evaluation result, with 3 cycles (288 hours) or more being considered a pass. If no cracks were observed for more than 15 cycles, it was rated as "15". The maximum number of cycles for each example is shown in Tables 1 to 6 as the result for "Weather Resistance A".

[0121] [Weather resistance rating B] The SUV test was carried out under the same conditions as in the weather resistance evaluation A, and a cellophane tape adhesion test was carried out on the surface of the evaluation sample every 96 hours. In the cellophane tape adhesion test, the surface condition after the peel test was visually observed, and if peeling was observed, the number of cycles that had elapsed at that point was used as the evaluation result, with 3 cycles (288 hours) or more being considered a pass. If no peeling was observed even after 15 cycles, it was rated as "15". The maximum number of cycles for each example is shown in Tables 1 to 6 as the result for "Weather Resistance B".

[0122] [Table 1]

[0123] [Table 2]

[0124] [Table 3]

[0125] [Table 4]

[0126] [Table 5]

[0127] [Table 6]

[0128] The abbreviations shown in Tables 1 to 6 respectively represent the following compounds or the compounds obtained in the above-mentioned synthesis examples. 1,4-BDA: 1,4-butanediol diacrylate 1,6-HDA: 1,6-Hexanediol diacrylate 1,9-NDA: 1,9-nonanediol diacrylate, 1,10-DDA: 1,10-decanediol diacrylate DPGDA: Dipropylene glycol diacrylate (manufactured by Daicel Allnex) A-200: Polyethylene glycol diacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.) A-DCP: Tricyclodecane dimethanol diacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.) A9300: Tris(2-acryloxyethyl)isocyanurate (manufactured by Shin-Nakamura Chemical Co., Ltd.) A9300-CL: Caprolactone-modified tris(2-acryloxyethyl)isocyanurate (manufactured by Shin-Nakamura Chemical Co., Ltd.) TEMPTA: Trimethylolpropane triacrylate (manufactured by Daicel Allnex) DPHA: Dipentaerythritol hexaacrylate (KAYARAD DPHA, manufactured by Nippon Kayaku Co., Ltd.) DPCA-20: Caprolactone-modified dipentaerythritol hexaacrylate (KAYARAD DPCA-20, manufactured by Nippon Kayaku Co., Ltd.) DPCA-60: Caprolactone-modified dipentaerythritol hexaacrylate (KAYARAD DPCA-60, manufactured by Nippon Kayaku Co., Ltd.) Tinuvin123: HALS "Tinuvin123" (product name, manufactured by BASF) Tinuvin152: HALS "Tinuvin152" (product name, manufactured by BASF) LA-82: HALS "ADEKA STAB LA-82" (product name, manufactured by ADEKA) LA-46: UV absorber "ADEKA STAB LA-46" (product name, manufactured by ADEKA Corporation) Tinuvin479: UV absorber "Tinuvin479" (product name, manufactured by BASF) Ruva-93: UV absorber "Ruva-93" (product name, manufactured by Otsuka Chemical Co., Ltd.) PE: Polyester resin-coated steel plate (a substrate made by applying white polyester-isocyanate paint with a pigment mass concentration (PWC) of 60% to the surface of a zinc-treated steel plate with a thickness of 2 mm so that the dry film thickness is 30 to 40 μm, and then heat-curing the paint at 80°C for 30 minutes, substrate thickness 2 mm) PC: Polycarbonate resin base material (Teijin Panlite L-1225ZL, thickness 3 mm) ABS: ABS resin base material (Nippon A&L "Clarastic GA-701 JH22", thickness 3 mm) AU: Acrylic urethane resin-coated steel plate (a white acrylic urethane paint with a PWC of 60% is applied to the surface of a zinc-treated steel plate with a thickness of 2 mm so that the dry film thickness is 30 to 40 μm, and the paint is heat-cured at 80 ° C for 30 minutes, substrate thickness 2 mm) EP: Epoxy resin-coated steel plate (a white acid-epoxy curing paint with 60% PWC is applied to the surface of a 2 mm-thick zinc-treated steel plate so that the dry film thickness is 30 to 40 μm, and the paint is heat-cured at 80 ° C for 30 minutes, substrate thickness 2 mm)

[0129] From the results of Examples 1 to 44, it was confirmed that the cured coating of the active energy ray-curable composition of the present invention was excellent in appearance, chemical resistance, weather resistance, and adhesion. On the other hand, it was confirmed that Comparative Examples 1 to 5, which did not contain any of the components, were inferior in at least one of the properties.

[0130] (Example 45) The active energy ray-curable composition of Example 2 was applied to the same polyester resin-coated steel sheet substrate as above using a bar coater, dried at 80°C for 4 minutes, and then irradiated with an ultraviolet ray irradiation device (GS-YUASA, high-pressure mercury lamp) under atmospheric pressure at an illuminance of 200 mW / cm. 2 , the irradiation light amount 1 (unit: mJ / cm 2 ) to obtain a laminate having a coating film with a thickness of 10 μm. Furthermore, the same active energy ray-curable composition was applied onto the obtained coating film using a bar coater, dried at 80°C for 4 minutes, and then irradiated with a similar ultraviolet ray irradiation device under atmospheric conditions at an illuminance of 200 mW / cm 2 , the irradiation light amount 2 (unit: mJ / cm 2 ) to obtain a laminate having a cured coating with a total thickness of 20 μm.

[0131] (Examples 46 to 50, Comparative Examples 6 to 9) The active energy ray-curable compositions of the examples or comparative examples shown in Tables 7 to 8 were used, and laminates of each example were obtained in the same manner as in Example 45, except that the irradiation amount was changed to 1 or 2 in Tables 7 to 8.

[0132] The obtained laminates of each example were used as evaluation samples and were subjected to appearance evaluation, chemical resistance evaluation, and weather resistance evaluations A and B in the same manner as in Example 1. The results are shown in Tables 7 and 8. Note that in the weather resistance evaluation B of Comparative Example 8, peeling was observed before the start of the test, so the result was set to "0."

[0133] [Table 7]

[0134] [Table 8]

[0135] From the results of Examples 45 to 50, it was confirmed that the cured coating of the active energy ray-curable composition of the present invention was excellent in appearance, chemical resistance, weather resistance, and adhesion, whereas Comparative Examples 6 to 9 were confirmed to be inferior in at least one of the properties.

Claims

1. The composition comprises a compound (A) having a chain hydrocarbon group having 2 to 12 carbon atoms and two (meth)acryloyloxy groups, a urethane (meth)acrylate compound (B) having an isocyanurate bond or an allophanate bond, and a (meth)acrylate compound (C) having an isocyanurate bond, The active energy ray-curable composition, wherein the (meth)acrylate compound (C) is a compound other than the urethane (meth)acrylate compound (B), has no urethane bond, and has an isocyanurate bond and a (meth)acrylate structure.

2. The urethane (meth)acrylate compound (B) having an isocyanurate bond or an allophanate bond has, in addition to the isocyanurate bond, the allophanate bond and the (meth)acryloyl group, —O—C(═O)—(CH 2 ) nA (nA represents an integer of 1 to 6), and a compound (B1) having, in addition to an isocyanurate bond, an allophanate bond, and a (meth)acryloyl group, —O—C(═O)—(CH 2 ) nA (nA represents an integer of 1 to 6).

3. The active energy ray-curable composition according to claim 1 , further comprising a compound (D) containing four or more (meth)acryloyl groups in one molecule.

4. 2. The active energy ray-curable composition according to claim 1, wherein the active energy ray-curable composition does not contain an organic solvent or contains an organic solvent in an amount of 30 mass% or less based on the total amount of the composition.

5. A laminate having a cured layer of the active energy ray-curable composition according to any one of claims 1 to 4.

6. A step 1 of applying the active energy ray-curable composition according to any one of claims 1 to 4 onto a substrate to obtain a coating film; and A method for producing a laminate, comprising the step 2 of irradiating the coating film with active energy rays to partially or entirely cure the coating film.

7. The method for producing a laminate according to claim 6 , further comprising repeating steps 1 and 2 in this order at least once after step 2.

Citation Information

Patent Citations

  • Active energy ray-curable composition and laminate

    JP2013010921A

  • Curable resin composition, resin cured product, laminated film, transfer film, and laminate

    JP2020193256A

  • JPP7454777B

  • Photocurable resin composition, cured coating film, and molded article with cured coating film

    WO2022025175A1

  • Antireflection film, laminate having antireflection film, and method for manufacturing antireflection film

    WO2022255340A1